ABC News/Good Housekeeping Mother's Day Poll, January 2006 ([Verlag nicht ermittelbar], 2007)
This special topic poll, conducted January 30-February 2, 2006, is part of a continuing series of monthly polls that solicit public opinion on the presidency and on a range of other political and social issues. The focus of this data collection was on respondents' experiences as mothers. Female respondents with children under the age of 18 were asked how well they felt they were doing as mothers, how much each worried about not being as good a mother as she would like to be, and the quality of her relationships with her children and with her own mother. The poll asked how often the respondent asked her mother for advice, whether her mother ever gave her unsolicited parenting advice, and whether she found this advice helpful or annoying. A series of questions asked respondents to compare their own parenting styles with that of their mothers in areas such as discipline and parental involvement, and respondents gave their opinions on whether being a mother was harder or easier compared to when they were children. Additionally, respondents were asked whether they worked outside the home, whether they considered their work to be a career or just a job, who had the main child care responsibilities in their households, whether their own mothers had worked outside the home when they were children, and the number of children in their families when they were growing up. Demographic variables include age, race, marital status, household income, employment status, education level, and number and ages of children in the household.